Predictive Value of the Neutrophil-Lymphocyte Ratio for Tumor Regression Grade and Prognosis of Local Advanced Rectal Cancer Patients Undergoing Neoadjuvant Chemoradiotherapy - Shuofeng Li MD; Dingyuan Wang MD; Ran Wei MD; Guanhua Yu MS; Xishan Wang MD; Zheng Jiang MD (Technology in Cancer Research & Treatment, 2023)
Purpose Numerous indicators can be used to predict tumor patients’ prognosis and tumor regression grade (TRG). The role of the neutrophil-lymphocyte ratio (NLR) among individuals with locally advanced rectal cancer (LARC) following neoadjuvant chemoradiotherapy (nCRT) hasn't been studied, nevertheless. This study aims to explore the predictive value of the NLR before nCRT (pre-NLR) in TRG and prognosis of LARC patients undergoing nCRT.. Methods In this retrospective investigation, 326 LARC patients receiving nCRT in total were included. The link between the pre-NLR and TRG was examined using a logistic regression analysis. A Cox-based nomogram was created in the meanwhile to forecast overall survival (OS). With the use of calibration plots and receiver operating characteristic (ROC) curves, we evaluated the nomogram's predictive capabilities. Results The median pre-NLR across 326 patients was 2.2 (interquartile range, IQR: 1.7-2.7). In the logistic regression analysis, only the pre-NLR for TRG in LARC patients receiving nCRT was statistically significant (odds ratio, OR = 0.62, 95% CI: 0.47-0.80, P < 0.001). Pre-NLR, nCRT with surgery interval, ypTNM stage, TRG, vascular invasion, adjuvant chemotherapy, and carbohydrate antigen 19–9 before nCRT were revealed to be OS predictors in the Cox multivariate analysis. According to calibration plots and ROC curves, the predictive nomogram demonstrated high statistical performance on internal validation. Conclusion This study demonstrated that a lower pre-NLR was probably associated with a greater rate of TRG in LARC patients undergoing nCRT. Furthermore, the pre-NLR was credibly correlated with OS in LARC patients undergoing nCRT. Meanwhile, we constructed a nomogram for predicting the prognosis in LARC patients undergoing nCRT.